Organizing America : stories of Americans who fought for justice - Loomis, Erik (The New Press, 2025)
"From the acclaimed author of A History of America in Ten Strikes, a sweeping account of the impact of organizers on United States history. We are living through a time when real social change seems to be in the rearview mirror. But this rousing new book offers a beacon of hope: the stories of organizers who have shown America the way forward in the darkest of times. Author of the celebrated A History of America in Ten Strikes (a Kirkus Reviews best book of 2018), Erik Loomis uncovers a rich and revealing history of social change activism with immediate relevance to our present. In twenty short biographies, Organizing America tells the story of America through its most important organizers. A chronological story with a vast sweep, Organizing America considers a cross section of social justice activists across time, race, gender, and movement, examining lives as varied as Benjamin Lay, Ida B. Wells, Eugene V. Debs, Elizabeth Gurley Flynn, Bob Moses, Yuri Kochiyama, Daniel Berrigan, Dolores Huerta, Barbara Gittings, and many more. With an introduction that explains what organizing is and how collective action works--and how we should think about the power of organizing in 2025 and beyond--Loomis sets a tone that is both practical and historical, providing context and inspiration for anyone seeking to step into the work of changing America for the better."-- Provided by publisher.